Acute toxicity and patient‐reported symptom score after conventional versus moderately hypofractionated proton therapy for prostate cancer. Issue 2 (19th October 2021) - Iizumi, Takashi; Ishikawa, Hitoshi; Sekino, Yuta; Tanaka, Keiichi; Takizawa, Daichi; Makishima, Hirokazu; Numajiri, Haruko; Mizumoto, Masashi; Nakai, Kei; Okumura, Toshiyuki; Sakurai, Hideyuki
Abstract: Introduction: To confirm the feasibility of hypofractionated proton beam therapy (PBT), we compared the acute adverse event rates and International Prostate Symptom Score (IPSS) in prostate cancer patients treated with hypofractionated versus conventionally fractionated (2.0 Gy relative biological effectiveness (RBE)/fraction) PBT. Methods: We reviewed 289 patients with prostate cancer, of whom 73, 100, and 116 patients were treated with 2.0, 2.5, and 3.0 Gy (RBE)/fraction, respectively. The endpoints were acute genitourinary and gastrointestinal toxicities and the IPSS, evaluated up to 6 months after PBT initiation. Results: No significant differences were found in acute toxicity rates or the IPSS among the fractionation schedules. Diabetes mellitus, age, and androgen deprivation therapy were not identified as factors associated with the IPSS. Conclusion: There were no significant differences in adverse events or quality of life among the three fractionation schedules early after PBT. Abstract : The acute adverse event rates and International Prostate Symptom Score (IPSS) up to 6 months in 289 patients treated with hypofractionated (2.5 Gy or 3.0 relative biological effectiveness (RBE)/fraction) versus conventionally fractionated (2.0 Gy(RBE)/fraction) proton beam therapy (PBT). Although significant increases in the IPSS were observed at the end of PBT in all groups, the score had returned to the pre‐PBT value, and no significant differences were found in the acute adverse event rates or IPSS among the fractionation schedules early after PBT, suggesting that a shorter treatment course might have greater benefit for patients with localised prostate cancer.